Changes in Quality Traits and Oxidation Stability of Syzygium aromaticum Extract-Added Cooked Ground Beef during Frozen Storage - Mohammad Ashrafuzzaman Zahid; Jeong-Uk Eom; Rashida Parvin; Jin-Kyu Seo; Han-Sul Yang (MDPI AG, 2022)
This study was accomplished by comparing the oxidative stability of (0.1%) Syzygium aromaticum extract (SAE) and (0.02%) butylated hydroxytoluene (BHT)-added cooked ground beef with an antioxidant free-control sample during frozen storage. All samples showed a non-significant (p > 0.05) effect on pH, thawing loss, redness, and yellowness values during storage. Incorporation of BHT and SAE led to a significant (p < 0.05) reduction in thiobarbituric acid-reactive substances (TBARS) and volatile levels as an active antioxidant. The generation of less volatiles found in SAE-treated samples up to 6 months (p < 0.05) of storage. Therefore, SAE-protected ground beef can lead to lower lightness, lipid oxidation, and volatile compounds levels after cooking compared with control and BHT samples.